Citogenética comparativa em espécies de Hypostomus (Siluriformes, Loricariidae, Hypostominae). Contribuição da fração repetitiva do genoma para a diversidade cromossômica do grupo - Traldi, Josiane Baccarin (2012)
Hypostomus is the widest genus of the armored catfishes in South America. This group presents a great diversity in color pattern and morphology, and shows not conservative chromosomal features. Different classes of repetitive DNAs have distinct evolutionary dynamics in the genome of eukaryotes. Therefore, analyses and distribution of these sequences in chromosomes may provide important data about karyotype evolution and diversification. Given the large chromosomal variability of species of the genus Hypostomus, coupled with the valuable role of repetitive DNAs to elucidate evolutionary questions, this study aimed at contributing to the knowledge of the karyotype evolution of the genus Hypostomus, trying to understand the role of repetitive DNAs in this scenario. Classical cytogenetic analyses of Hypostomus ancistroides, Hypostomus iheringii, Hypostomus nigromaculatus e Hypostomus tapijara show that the diploid number, karyotype formula, heterochromatic distribution and location of ribosomic DNAs are widely variable in this group. In H. iheringii, it was identified a hetechromatic polymorphism, which is possibly related to the process of heterochromatinization. The present chromosomic characterization of H. iheringii and H. tapijara comprise the first cytogenetic studies in these species, which indicates the existence of a great unexplored diversity in this genus. In Hypostomus, few data concerning the location and characterization of repetitive sequences are available. The fluorescence in situ hybridization with rDNAs 18S and 5S probes showed different results for the four species, occurring simple, multiple and syntenic markings. The sites of (TTAGGG)n were restricted to the terminal portion of the arms of all chromosomes in H. ancistroides, H. nigromaculatus and H. tapijara, which corroborates the evolution pattern based on centric fissions proposed to Hypostomus. However, in H. iheringii, it was evidenced ITS sites (Interstitial Telomeric Site) on a chromosome pair, suggesting the presence of other chromosomal rearrangements in the evolution of the group, in addition to centric fissions. The sequence (GATA)n, the largest component of the Bkm satellite DNA, and the retrotransposons Rex1, vi Rex3 and Rex6 showed a dispersed pattern in all species, indicating the possible relationship of these sequences with the great diversity of Hypostomus karyotype.